2019
DOI: 10.3389/fcvm.2019.00150
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Multifaceted Roles of STAT3 in the Heart

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a signaling molecule and transcription factor that plays important protective roles in the heart. The protection mediated by STAT3 is attributed to its genomic actions as a transcription factor and other non-genomic roles targeting mitochondrial function and autophagy. As a transcription factor, STAT3 upregulates genes that are anti-oxidative, anti-apoptotic, and pro-angiogenic, but suppresses anti-inflammatory and anti-fibrotic genes. Its suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 188 publications
(239 reference statements)
4
84
0
2
Order By: Relevance
“…To understand the mechnisms by which STAT3 contributes to protection of EAP against I/R imjury, we determined the apoptotic and survival signaling in the heart tissue of the mice. STAT3 is involved in decreasing cardiac I/R injury by reducing apoptosis or increasing anti-apoptotic signaling, increasing expression of cardioprotective proteins, decreasing ROS generation, and inhibiting autophagy (Harhous et al, 2019). We found that EAP promoted the expression of anti-apoptotic proteins Bcl-2 and Bcl-xl and p-AKT in the Stat5 fl/fl +I/R mice, but not in the Stat5-cKO+I/R mice.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…To understand the mechnisms by which STAT3 contributes to protection of EAP against I/R imjury, we determined the apoptotic and survival signaling in the heart tissue of the mice. STAT3 is involved in decreasing cardiac I/R injury by reducing apoptosis or increasing anti-apoptotic signaling, increasing expression of cardioprotective proteins, decreasing ROS generation, and inhibiting autophagy (Harhous et al, 2019). We found that EAP promoted the expression of anti-apoptotic proteins Bcl-2 and Bcl-xl and p-AKT in the Stat5 fl/fl +I/R mice, but not in the Stat5-cKO+I/R mice.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies have also shown that the IL-6 and IL-10 family of cytokines are the main mediators that activate intrinsic JAK/STAT3 signaling to induce the transcription of genes enabling survival and proliferation of cells (Harhous et al, 2019;Huynh et al, 2017) . Activated STAT3 can regulate the expression of genes (such as MMP2, MMP9, and Ubc13) and therefore underpin the molecular cross-talk between these genes (Pipicz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized the gene expression data to infer the disease related gene expression to identify candidate regulatory genes and to infer signaling pathway networks directly from candidate genes expression. According to DisGeNET database, role of 17 hub and bottleneck genes in MI is supported by many experimental work across the globe [52][53][54][55][55][56][57][58][59][60][61][62][63] including VEGFA, which limits myocardial damage in MI animal models [63], ICAM1, implicated in pathophysiologic responses and neutrophil in ltration [55,61], TLR4 that mediates maladaptive left ventricular remodeling and impairs cardiac function [62]. Interleukins family members such as IL1A and IL1B as well as PTGS2 which will be discussed further below.…”
Section: Discussionmentioning
confidence: 99%
“…ÎČ-MHC forms the heavy chain structure of type II myosin in sarcomeres, which in a sliding mechanism with actin filaments, generates the mechanical forces needed for muscle contraction. Mutations in the STAT3 gene have also been found to contribute to PPCM ( Ballard, 2019 ; Harhous et al, 2019 ). Other genes in which mutations have been reported to be associated with PPCM onset and progression include truncations in DMD (dystrophin that causes Duchenne’s Muscular Dystrophy) ( Cheng and Prior, 2013 ; Ahmed et al, 2016 ), DSP (desmoplakin) ( Ware et al, 2016 ), TPM1 (α-tropomyosin)( Ware et al, 2016 ), and missense mutations in MYBPC3 (cardiac myosin binding protein C) ( Morales et al, 2010 ), TNNC1 (cardiac troponin C) ( Mestroni et al, 1994 ), TNNT2 (cardiac troponin T) ( Morales et al, 2010 ), and LAMP2 (lysosome-associated membrane protein) ( Ware et al, 2016 ).…”
Section: Dilated Cardiomyopathy and Mitochondrial Dysfunctionmentioning
confidence: 99%